West view of the interior of the Chapel of St. Bartholomew the Great, West Smithfield - Shepherd, Thomas Hosmer; Dale (Tufts Archival Research Center, 2008)
As used for the meeting-house of Mr. John Latchford. This illustration is from Robert Wilkinson's "Londina Illustrata," vol. 1.